2021
DOI: 10.1021/acs.jpcc.1c05937
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Oriented Attachment of Gold Nanoparticles by Size and Shape

Abstract: The concept of nanoparticles (NPs) as building blocks offers new possibilities to produce complex and tailored structures from the nano- to the mesoscale. In order to control a “polymerization” of particles, knowledge of the mechanism and kinetics of the reaction are necessary. We show that controlled assembly of cetylpyridinium chloride-stabilized gold NPs utilizing induced dipole–dipole interactions can lead to the formation of defined one-dimensional structures in solution. Three different shaped NPs (cubes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 31 publications
1
12
0
2
Order By: Relevance
“…According to this set of experimental evidence, the anisotropic growth of NCs may be divided in two stages (Figure G), with the first one occurring just after photofragmentation generating the initial NCs, followed by a second slower one taking place over several days in which the NCs coalesce and increase their aspect ratio. This is in agreement with previous observations of unidirectional self-assembly of metallic nanoparticles, which occurs with the fast formation of oligomers followed by their slower assembly into larger structures. ,,,, …”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…According to this set of experimental evidence, the anisotropic growth of NCs may be divided in two stages (Figure G), with the first one occurring just after photofragmentation generating the initial NCs, followed by a second slower one taking place over several days in which the NCs coalesce and increase their aspect ratio. This is in agreement with previous observations of unidirectional self-assembly of metallic nanoparticles, which occurs with the fast formation of oligomers followed by their slower assembly into larger structures. ,,,, …”
Section: Resultssupporting
confidence: 93%
“…Besides, in the NCs with appreciable broadband absorption, the longitudinal size extends well beyond the transversal size and, in part, also beyond the diameter of the initial NPs. This is a clear indication that, after photofragmentation, the small metal particles preferentially regrew in a unidirectional way, as a consequence of the balance between the attractive dipolar interactions in the colloidal system and the electrostatic repulsion forces, which are weaker along the axis of an elongated particle (e.g., after sticking of two nanospheres). ,,, …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…53 During the nucleation and self-assembly process, a shift and broadening of the longitudinal plasmon bands for all investigated nanorod colloids were observed, meaning new bands corresponding to the formation of aggregates emerged at longer wavelengths. 50,54,55 Overall, these results indicate the suitability of using ethanol to trigger the aggregation of CTAB-stabilised gold nanorods. Moreover, analysis of the destabilization kinetics showed that the reactions proceeded as a second-order reaction (ESI Table S1†).…”
Section: Resultsmentioning
confidence: 70%